Biotransformação dos ácidos gálico e elágico por microorganismos do cerrado brasileiro - Silva, Liliane de Sousa (2015)
The gallic acid (GA) and its derived ellagic acid (EA) are widely distributed in nature tannins, present in tea, red wine, fruit, drinks and various medicinal plants. AG and AE are known to have anti inflammatory properties, antimutagenic, anticancerígenica and antioxidant activity. To produce functionalized derivatives of such compounds by biotransformation with filamentous fungi is an efficient and sustainable alternative, due to their ability to catalyze further reactions regio and stereo-selective. The aim of this study was to apply strains of Cerrado in the biotransformation of AG and AE. For this Thin Layer Chromatography (TLC) and High Performance Liquid Chromatography (HPLC) to monitor the production of derivatives developed analytical methodologies. Five strains of the Brazilian Cerrado were selected, these are Beauveria sp. IP06, IP08, IP94, IP98 and IP153. Incubation was performed in two different culture media: Glucose and "corn steep" for 96 hours at 27 C and 200 rpm. At the end of incubation the extraction and purification of the derivatives was performed. All strains were effective for biotranformação compounds. The culture medium influenced quali-quantitatively the production of derivatives, "corn steep" provided greater variety of substrates for both derivatives. The obtained derivatives were characterized by MS, ¹H NMR, HSQC, HMBC, UV and CCD. Derivatives of fatty acids are: benzoic acid, 3-O-methyl-β-glucopyranosyl galatoester (Labiocon 465); benzoic acid, 4 - [[6-O- (3,4-dihydroxy-5-methoxybenzoic acid)-α-D-glucopyranoside]oxy]-3-hydroxy-5metoxi (Labiocon 484); gallic acid 3-O-β-glucopiranoside (510 Labiocon) and 3,4-dihydroxy-5-methoxy-benzoic acid 2-hydroxy-5-methoxycarbonyl-phenyl ester (Labiocon 530). The AE is derived from 3,8-Dimethoxy-dibenzo [b, d] pyran-6-one ellagic acid (511 Labiocon) and 4-O, 3'-O-methyl -β-D-glucose (Labiocon 534) .